Mentoring as Correlate of Productivity of Librarians in Universities in South-West Nigeria - Ossai-Ugbah, Ngozi Blessing; Akporhonor, Blessing Amina (Communicate: Journal of Library and Information Science, 2023)
The purpose of this study was to investigate mentoring on librarians’ productivity in universities in South-West Nigeria. The expo-facto research design was adopted for the study. The population of the study was 504 librarians in universities in South-West Nigeria drawn from 37 federal, state, and private universities in South-West Nigeria. The sample for the study is 504 librarians. Three research questions were raised and answered with two formulated hypotheses. The research instrument for data collection was the questionnaire. Data were collected and analysed. Frequency, percentages, mean, and standard deviation were used to answer the research questions. Pearson Product-Moment Correlation coefficient (PPMC) and Multiple Regressions, with the aid of Statistical Package for Social Sciences (SPSS) version 20 were used to test the hypotheses at 0.05 level of significance. The finding revealed that mentoring among librarians in South-West universities exists at a high level in career development, role modelling and psychosocial support. There was no significant relationship between mentoring and productivity of librarians in universities in South-West Nigeria. The researcher recommended that, since there was a high level of mentoring among librarians in universities in South-West Nigeria, the factors responsible for their low productivity should be investigated.